2016
DOI: 10.1038/srep21190
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 attenuates IL-1β induced alteration of anabolic and catabolic activities in intervertebral disc degeneration

Abstract: Intervertebral disc degeneration (IDD) is characterized by disordered extracellular matrix (ECM) metabolism, implicating subdued anabolism and enhanced catabolic activities in the nucleus pulposus (NP) of discs. Pro-inflammatory cytokines such as interleukin-1β (IL-1β) are considered to be potent mediators of ECM breakdown. Hemeoxygenase-1 (HO-1) has been reported to participate in cellular anti-inflammatory processes. The purpose of this study was to investigate HO-1 modulation of ECM metabolism in human NP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…We observed that human degenerative IVD nucleus pulposus tissues showed down-regulated expression of HO-1, up-regulated expression of P65, and increased apoptosis, and these results were consistent with previous studies [9, 16, 17]. Thus, we hypothesized that HO-1 and NF-κB may play a significant role in the process of NPC apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that human degenerative IVD nucleus pulposus tissues showed down-regulated expression of HO-1, up-regulated expression of P65, and increased apoptosis, and these results were consistent with previous studies [9, 16, 17]. Thus, we hypothesized that HO-1 and NF-κB may play a significant role in the process of NPC apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we observed that the number of apoptotic cells in the IDD group was greater than that in the LVF group. Simultaneously, Bo Hu et al [9] indicated that the expression levels of HO-1 in NP from severe IDD were lower than in those of NP from mild IDD. In our study, the numbers of HO-1-positive cells in the IDD group were significantly decreased compared with the LVF group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells from NP tissue were extracted according to a previous study [40,41], specimens were minced and incubated with 2 U/mL protease (Pronase; Sigma-Aldrich, St Louis, MO, USA) in serum-free DMEM/F12 medium (Gibco, Grand Island, NY, USA) for 30 min at 37 °C after washing twice in PBS. The digested cells were then incubated with 0.25 mg/mL type II collagenase (Gibco) for 4 h at 37 °C.…”
Section: Isolation Of Nucleus Pulposus Cellsmentioning
confidence: 99%
“…Intriguingly, the results are not always consistent between studies, and such problems can be caused by sample variation or other regional factors. Moreover, recent studies purpose that post-transcription and translational regulation are important ways to affect the gene expression in IDD, add to the complexity of the mechanism network of IDD (14). Thus, more precise global expression data are needed before focusing on the detailed mechanism of each gene.…”
mentioning
confidence: 99%